Low-Dimensional Nanoparticle Clustering in Polymer Micelles and Their Transverse Relaxivity Rates - Hickey, Robert J. (ACS Nano, 2013)
One- or two-dimensional arrays of iron oxide nanoparticles were formed in colloidal assemblies of amphiphilic polymers. Electron tomography imaging revealed that nanoparticles are arranged into one-dimensional strings in magneto-micelles or two-dimensional sheets in magneto-core/shell assemblies. The distinct directional assembly behavior was attributed to the interparticle interaction relative to the nanoparticle–polymer interaction, which was modulated by varying the cosolvent used for the solution phase self-assembly. Magneto-core/shell assemblies with varying structural parameters were formed with a range of different sized as-synthesized nanoparticles. The transverse magnetic relaxivity rates (r2) of a series of different assemblies were determined to examine the effect of nanoparticle arrangement on the magnetic relaxivity for their potential applications in MRI. The results indicated that the assembly structure of nanoparticles in polymer micelles significantly affects the r2 of surrounding water, providing a way to control magnetic relaxivity.